Practical use of goat milk and colostrum - Voloshina, Iryna; Soloshenko, Kateryna; Lych (Tkachenko), Inna; Shkotova, Lyudmila (My University, 2021)
This review presents the protein and amino acid composition of both goat colostrums and milk and describes the properties of goat colostrums and milk components. In addition, the prospects of use of goat milk and colostrum in the food and cosmetics industry and the feasibility of use of goat milk for baby feeding are shown. Functional foods produced from goat milk have antioxidant, anti-inflammatory, cardioprotective, antihypertensive and antiatherogenic activities in the human body. Goat milk cosmetics are very useful for maintaining a healthy skin and are effective in treatment of various skin diseases. Infant formula based on goat milk provides comfortable digestion for babies and are better at absorbing proteins, fats and other nutrients than infant formula based on cow’s milk.

В огляді наведено інформацію стосовно протеїнового й амінокислотного складу козиного молозива та молока, проаналізовано властивості компонентів молозива та молока кіз. Окрім цього, показано перспективи застосування козиного молока та молозива у харчовій і косметичній промисловості, доцільність використання козиного молока для дитячого вигодовування. Функціональні харчові продукти з козиного молока виявляють антиоксидантні, протизапальні, кардіопротекторні, антигіпертензивні та антиатерогенні властивості в організмі людини. Косметичні засоби на основі козиного молока є дуже корисними для підтримання здорового вигляду шкіри і ефективними у лікуванні різних захворювань шкіри. Дитячі суміші на основі козиного молока забезпечують комфортне травлення у немовлят і є кращими у засвоюванні протеїнів, жирів та інших поживних речовин порівняно із сумішами з коров’ячого молока.
Keywords: goat colostrum; goat milk; proteins; amino acids; cosmetology; baby feeding; козине молоко; протеїни; амінокислоти; косметологія; дитяче харчування; кафедра біотехнології і мікробіології